PENINGKATAN ANGKA KONSUMSI IKAN PROVINSI JAWA TIMUR MELALUI PENGENALAN IKAN-IKAN KONSUMSI DAN PRODUK OLAHAN PERIKANAN PADA BALITA - Rhochmad Wahyu Illahi; Gilang Rusrita Aida; M Tajuddin Noor; Rosidah Wahyu Ningtyas; Angga Pratama Putra; Exist Saraswati; Mirza Ramadhani (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
Fisheries have an important role in society, one of which is as a food source rich in nutritional content and animal protein. Even though the fishery potential in Indonesia is very high, in fact, in several areas, the level of fish consumption is still below the national fish consumption level, one of which is in East Java. This is very ironic when compared with the fact that in 2022 East Java was the province with the highest capture fisheries production in Indonesia. Efforts that can be made to increase fish consumption in East Java are by introducing the types of fish consumed, both freshwater fish and sea fish, and introducing processed fishery products to toddlers. The method of implementing this community service activity consists of 3 (three) stages, i.e. the preparation, implementation, and reporting stages. During the implementation, the participants showed quite high enthusiasm because the event was packaged by leading illustrations accompanied by children's songs about fish. The results of the community service activities can be seen from an increase in the preferences to eat fish and an increase in toddlers' knowledge of the types of freshwater and marine fish that can be consumed.